Direct ligand screening against membrane proteins on live cells enabled by DNA-programmed affinity labelling. Issue 31 (17th March 2021) - Huang, Yiran; Deng, Yuqing; Zhang, Jianfu; Meng, Ling; Li, Xiaoyu
Abstract : DNA-programmed affinity labelling (DPAL) enables the screening of chemical compounds against membrane proteins directly on live cells. Abstract : Membrane proteins are important drug targets; however, ligand discovery for membrane proteins is highly challenging due to their hydrophobic nature. We show that membrane proteins may be specifically labelled with a DNA tag by DNA-programmed affinity labelling (DPAL), thereby enabling the screening of chemical compounds against membrane proteins directly on live cells.